Effects of employee gender, occupational prestige, and gender concentration on impression judgments about employees - Strife, Samantha R., author; Dik, Bryan, advisor (Colorado State University. Libraries, 2009)
A vignette strategy was employed to assess how occupational prestige and gender interact to influence overall judgment of target employees. Specifically, ambiguous vignettes were utilized to determine the extent to which attributions associated with occupationism (i.e., prejudicial attitudes towards an individual based on occupational membership) were present for a sample of undergraduate students. Level of occupational prestige (high vs. low), gender concentration of occupation (predominately "female," predominately "male," gender balanced), and gender of employee (female vs. male) were manipulated in the vignettes to ascertain judgments about individuals in varied occupational settings. In addition, stereotypic gender role characteristics were assessed to determine how measurements of masculinity and femininity relate to overall impression of target employee. There were no significant main effects or two way interactions found for occupational prestige, gender of the employee in the vignette, and gender constituency of the occupation. Results indicated that men in a predominately male, high prestige occupation were rated significantly more positively than females in the same predominately male, high prestige occupation. Furthermore, scores of masculinity and femininity were significantly correlated with participants' overall impression of the target employee, such that stereotypic traits associated with masculinity and femininity of the target employee were related to higher ratings of the employee. Implications of the findings are explored using role congruity theory and social role theory.
Keywords: gender; impression judgments; occupationism; prestige